Evaluation of Prospective Science and Technology Teachers' Experiences of Project Management - (:unkn) unknown (HACETTEPE UNIV, 2013)
In this study it is aimed that; the prospective science teachers can find an opportunity to make projects with the pupils in the schools, and the science projects which are not being conducted commonly in secondary schools, can be done by the pupils in the schools. The study made for this purpose comprises of management of science projects under the course of Social Service Applications for the prospective science teachers in a university in Istanbul during the spring semesters of 2009-2010 and 2010-2011 educational years and the science projects done by the 6th grade pupils during 2010-2011 educational year. Application was evaluated by asking open-ended questions to 24 prospective science teachers at the end of the application. The development of the scientific process skills of both groups those were conducted and did not conducted science projects from 6th grades in 2010-2011 educational year, was analyzed by using the scientific process skills test with a pre-test and pos-test application. When the opinions of the prospective teachers about the application are evaluated in general, it is convinced that; there is a big difference between conducting a project and managing a project; it is a very gainful experience to have such an opportunity, before especially graduation, by carrying out project management and doing this with the students one-to- one. According to the results of applied scientific process skills test, the average value of the posttest of the control group showed a meaningful decrease related to the pre-test average value. When the pretest-posttest averages of the experiment group are compared, the posttest values showed an increase, though not meaningful. Between the posttest scores of the control and experiment groups, it is found a meaningful difference to the experiment group's favour.
Keywords: Science and technology prospective teachers; project management; project-based learning; social service applications.